2000
DOI: 10.1007/s004210050042
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular responses at the onset of passive leg cycle exercise in paraplegics with spinal cord injury

Abstract: The purpose of this study was to examine the cardiovascular responses at the onset of passive leg cycle exercise (PLCE) in paraplegics with spinal cord injury (PSCI) to investigate the increase in venous return from the paralyzed lower limbs during PLCE. Six male PSCI having lesions at levels ranging from T8 to L1 and five male able-bodied subjects (ABS) participated in this study. The subjects performed PLCE at pedalling frequencies of 40 rpm for 6 min. Cardiac output (Q(c)), stroke volume (SV) and heart rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…(Muraki et al . ) and more recently Ballaz et al . () reported that passive cycle exercise enhances both cardiac output and blood flow, but Ter Woerds et al .…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…(Muraki et al . ) and more recently Ballaz et al . () reported that passive cycle exercise enhances both cardiac output and blood flow, but Ter Woerds et al .…”
Section: Discussionmentioning
confidence: 83%
“…Passive movement studies examining subjects with a SCI have yielded conflicting results, with some studies revealing significant cardiac output and peripheral blood flow responses (Muraki et al . , Ballaz et al . ), while others have reported no LBF response in this population (Ter Woerds et al .…”
mentioning
confidence: 99%
“…One is to improve orthostatic hypotension, which is common in patients with spinal cord or traumatic brain injury. Venous return and, hence, cardiac output increase during passive leg cycle exercise in healthy and in subjects with spinal cord injuries [14]. Similar effects are observed with functional electrical stimulation to induce leg cycling [15].…”
Section: Discussionmentioning
confidence: 95%
“…In the exercising limbs, blood flow is primarily enhanced by vasodilation and venous ''muscle pump'' activity. Previous studies have suggested that the mechanical lengthening and shortening of the muscles during passive leg cycling promotes circulation within the lower limbs of both persons with paraplegia Muraki et al 1996Muraki et al , 2000 and able-bodied individuals (Nakazono and Miyamoto 1985;Nobrega et al 1994), with positive health benefits to the former.…”
Section: Passive Leg Cyclingmentioning
confidence: 99%